Normal Variant, Salivary Flow Rate, and Taste Sensitivity as Oral Health Profile in the Elderly Community in Surabaya: A Cross-sectional Study - Adiastuti Endah Parmadiati, -
Aim: To describe the teeth, normal variants of the mucosa, and taste sensitivity as predictors of oral health among the elderly. Materials and Methods: Thirty‑six elderly patients participated in this study. The oral health status was screened by decay, missing, and filling teeth index (DMF‑T), and salivary flow rate was measured with a spontaneous drooling method. Taste sensitivity was done using filter paper disk (FPD) taste testing, composed of four taste solutions: sucrose, tartaric acid, sodium chloride, and quinine hydrochloride (level 1–5). The differences between taste sensitivity and salivary flow rate were analyzed using one‑way analysis of variance (ANOVA), and least significant difference (LSD) for post hoc test with P < 0.05. Results: The DMF‑T index in the elderly was in the high category with score >6.6 (83.33%). The most sensitivity taste was bitter (94.44%), followed by salty (91.67%), sweet (81.00%), and sour (75.00%). Only salty and sweet taste, in most of subjects, able to detect in the left of anterior (P = 0.011) and right of posterior tongue (P = 0.038). Subjects with flow rate 0.1–0.5 mL/min were able to detect lower concentration of sweet taste than those with salivary flow rate 0.6–1.0mL/min (P = 0.029). Normal variants of the oral mucosa most commonly found in the elderly were coated tongue (55.56%) and fissured tongue (50.00%). Conclusion: The elderly community in this study had a poor oral health index with most subjects in the DMF‑T high category with score >6.6, but most salivary flow rates were still relatively normal. No significant taste sensitivity impairment was found in the elderly.